Mechanism of induction of immune tolerance in experimental autoimmune encephalomyelitis by combination treatment with fingolimod plus pathogenic autoantigen. Issue 1 (22nd August 2014) - Yoshida, Yuya; Mikami, Norihisa; Tsuji, Takumi; Takada, Yuki; Nakazawa, Yuka; Dan, Rie; Takatsuji, Miku; Fujita, Tetsuro; Tsujikawa, Kazutake; Kohno, Takeyuki
Abstract Objective We previously reported that relapse of experimental autoimmune encephalomyelitis (EAE) occurred approximately 1 week after discontinuation of fingolimod (FTY720), but combination treatment with FTY720 plus pathogenic autoantigen significantly suppressed occurrence of relapse. Here, we investigated the mechanism of this suppression. Methods EAE mice were treated from onset with FTY720 alone or in combination with an autoantigenic peptide of myelin oligodendrocyte glycoprotein 35(MEVGWYRSPFSRVVHLYRNGK)55 (MOG35‐55). Antigen‐specific T cell activity and T cell subpopulations were analyzed by using flow cytometric analysis. Spinal cords were excised and examined immunohistochemically. Results After treatment with FTY720 alone, CD4+ T cells from inguinal lymph nodes (LN) maintained activity towards pathogenic autoantigen. The percentage of CD4+CD44highCD62Llow (effector memory) T cells in inguinal LN was significantly increased. At day 8 after discontinuation, infiltration of CD3+ and CD4+ cells in spinal cords was significantly increased, and the absolute number of CD4+ T cells in inguinal LN was decreased. However, in the case of combination treatment, the absolute number of CD4+ T cells in inguinal LN remained unchanged, and infiltration of CD3+ and CD4+ cells was significantly suppressed. Conclusions As the number of CD4+ T cells in inguinal LN was unchanged in the FTY720 plus MOG35‐55 group, the combination treatment might inhibit relapse by decreasing the ability of pathogenic T cells to migrate from peripheral tissues to the central nervous system. The combination treatment might become a breakthrough remission‐induction treatment for MS.